Penyuluhan Pembuatan Biopori Sebagai Solusi Alternatif Meminimalisir Banjir Di Kelurahan Kenali Besar Kota Jambi - Edwin Permana; Ratih Dyah Puspitasari; Ngatijo; Nelson; Faizar Farid; Diah Riski Gusti; Intan Lestari; Maharani; Moh Nabawi; Tri Siswanto (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Jambi is one of the provinces in Sumatra which has the potential of abundant natural resources. This must be based on the principles of sustainability, harmony, and best use, as well as the utilization of natural resources in the form of land and water as one of the basic assets of national development to achieve economic and ecological balance. Human activities by building buildings or other facilities without taking into account the area of ​​open land have resulted in reduced rainwater catchment areas. Another cause is the disposal of garbage in the flow of water bodies, so that water cannot flow smoothly which in turn results in overflow of water. Rainwater that becomes run off and garbage that is thrown carelessly, is then managed in a way so that it can be beneficial for the environment and humans themselves. Therefore, the idea of ​​making biopore infiltration holes arose where the main ingredient was organic waste. Partner priority problems are frequent flooding during the rainy season; the surrounding community does not have special skills to be able to make biopores as infiltration holes. The activity will be carried out using structured mentoring and training methods for making biopore infiltration holes. It is hoped that from this activity Partners can make biopori, activity videos and media article.